2017
DOI: 10.1159/000478534
|View full text |Cite
|
Sign up to set email alerts
|

Ist Negativsymptomatik bei Schizophrenie überhaupt behandelbar? Ein systematisches Literaturreview zur Wirksamkeit psychotherapeutischer Interventionen für Negativsymptomatik

Abstract: Die Negativsymptomatik stellt einen der bedeutendsten Prädiktoren für Einschränkungen im Funktionsniveau von Menschen mit Schizophrenie dar. Allerdings wird dieser Symptombereich weitgehend als nicht behandelbar wahrgenommen. In diesem Artikel hinterfragen wir dieses Vorurteil, indem wir die Ergebnisse der existierenden Wirksamkeitsstudien für Behandlungsprogramme für Negativsymptomatik zusammenstellen. Wir beschränkten uns bei unserer systematischen Literatursuche ausschließlich auf Studien, die die Negativsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(84 reference statements)
0
8
1
Order By: Relevance
“…One example of an already existing psychological intervention is social skills training, where there has been mixed evidence as to whether or not it is effective for reducing negative symptoms. However, no study so far has tested the effects of social skills training specifically for patients with ENS . In the light of the findings of this study, it could be expected that patients with low levels of ENS are in less need of an intervention in the interactional domain given their relatively normal social performance skills.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…One example of an already existing psychological intervention is social skills training, where there has been mixed evidence as to whether or not it is effective for reducing negative symptoms. However, no study so far has tested the effects of social skills training specifically for patients with ENS . In the light of the findings of this study, it could be expected that patients with low levels of ENS are in less need of an intervention in the interactional domain given their relatively normal social performance skills.…”
Section: Discussioncontrasting
confidence: 64%
“…avolition, anhedonia, and asociality) based on a wealth of factor analytic studies and subsequent expert consensus . However, whereas aetiological modelling and the potentials for treatment of MNS have been the focus of recent research efforts, there are neither viable aetiological models of ENS nor reliably effective treatments .…”
Section: Introductionmentioning
confidence: 99%
“…A large meta-analysis found that pharmacological treatments had very limited impact, if any at all (Fusar-Poli et al, 2015). As for nonpharmacological interventions, some show a limited impact (Lutgens, Gariepy, & Malla, 2017), while others show more encouraging findings (Riehle, Pillny, & Lincoln, 2017). These mixed results can be explained by a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Disappointingly though, they have proven notoriously difficult to treat. Recent reviews of the effectiveness of interventions aimed at negative symptoms report some positive effects of cognitive therapy and various skill trainings but the findings are mixed and the small effects can rarely be replicated in samples of patients with more pronounced negative symptoms (Aleman et al, 2017 ; Riehle et al, 2017 ). Similarly, despite a couple of promising studies, biological approaches, such as medication and electromagnetic neurostimulation have not been successful in reducing negative symptoms and there is even some indication that antipsychotics can potentially aggravate negative symptoms (Aleman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a frequent target has been neurocognitive impairment that is known to be associated with negative symptoms (Ventura et al, 2009 ; Strauss et al, 2012 ). However, despite producing improvements on neurocognition, cognitive remediation on its own has small effects—at the most—on negative symptoms (Elis et al, 2013 ; Cella et al, 2017 ; Riehle et al, 2017 ). Interestingly, however, its effects appear to be somewhat stronger if it is administered along with additional components that address social skills or problem solving (Roder et al, 2011 ; Eak et al, 2013 ; Mueller et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%